Perancangan Alat Bantu untuk Optimalisasi Proses Produksi Sayap Cover Blower di CV. DEF - Arrozaqqul Majid; Kardiman Kardiman; Rizal Hanifi (Jurnal Ilmiah Wahana Pendidikan, 2022)
A rice drying machine is a machine that functions to dry rice where the working system uses a blower and also a heating furnace to channel hot air which ultimately dries the rice in the drying process, the rice is placed in a holding tank where at the bottom of the reservoir there is space or a cavity to channel hot air. fired by a blower. The components in the Rice Dryer Machine are Blower, Cover Blower, Shaft and Frame. In the rice dryer blower there are wings that surround the cover which functions to concentrate the air going to the blower to be fired, the wings on this blower cover must have the same length and width. suitable for optimizing the work process on the blower. This research aims to make malls or tools that can be used to make it easier for workers to make wings so that the production process runs more optimally and the wings made will be more precise. The data obtained from the research is by measuring the object using a measuring instrument and then conducting a case study to find data on the specifications and components of the rice dryer. The results obtained from this design are the length of the mall is 39.25 cm, the height of the mall is 3.925 cm, the angle of the mall is 45°, the number of wings to surround the cover is 8 wings, the overall time of making the wings after using the mall is 2.880 seconds, the materials used namely Black Iron Plate / Base Plate. From the calculation of the overall time of making the wings before using the mall, it takes 4,800 seconds and it can be concluded that after the design of the mall/tools the time of making the wings becomes much faster.